Aluminum metallization and wire bonding aging in power MOSFET modules. (2018) - Ruffilli, R.; Berkani, M.; Dupuy, P.; Lefebvre, S.; Weber, Y.; Warot-Fonrose, B.; Marcelot, C.; Legros, M.
Abstract: A limiting factor for the long-term reliability of power MOSFET-based devices is the electro-thermal and/or thermo-mechanical aging of the metallic parts. Here, we assess the bonding wire and source metallization degradation of power devices, designed for applications in the automotive industry. Our approach consists in characterizing the metal microstructure before and after accelerated aging tests, by scanning electron microscopy, ion milling and microscopy, focused ion beam tomography, transmission electron microscopy and grain structure mapping. To focus on the wire-metallization bonding interface, we have set up a dedicated sample preparation that allows us to disclose the metallization under the bonding wires. This critical location is significantly different from the naked metallization, as the bonding process induces plastic deformation prior to aging. The main mechanism behind the device failure is the generation and propagation of fatigue cracks in the aluminum metallization. Away and under the wire bonds, they run perpendicularly from the surface down to the silicon substrate following the grain boundaries, due to an enhanced self-diffusion of aluminum atoms. Moreover, initial imperfections in the wire-metallization bonding (small cavities and aluminum oxide residues) are the starting point for harmful cracks that propagate along the wire-metallization interface and can eventually cause the wire lift-off. These phenomena can explain the local increase in the device resistance occurring at failure.